The impact of medical and nursing home expenses and social insurance policies on savings and inequality - Karen A. Kopecky; Tatyana Koreshkova (Federal Reserve Bank of Atlanta, 2010)
We consider a life-cycle model with idiosyncratic risk in labor earnings, out-of-pocket medical and nursing home expenses, and survival. Partial insurance is available through welfare, Medicaid, and social security. Calibrating the model to the United States, we find that 12 percent of aggregate savings is accumulated to finance and self-insure against old-age health expenses given the absence of complete public health care for the elderly and that nursing home expenses play an important role in the savings of the wealthy and on aggregate. Moreover, we find that the aggregate and distributional effects of public health care provision are highly dependent on the availability of other programs making up the social insurance system.
Keywords: E21; H31; H53; I18; I38; 330; out-of-pocket medical expenses; nursing home costs; means-tested social insurance; life-cycle savings; wealth inequality; social security